Early complications and cement leakage in elderly patients who have undergone intraoperative computed tomography (CT)-guided cement augmented pedicle screw placement: eight-year xingle-center experience - Ishak, Basem; Bajwa, Awais Akbar; Schneider, Till M.; Tubbs, R. Shane; Iwanaga, Joe; Ramey, Wyatt L.; Unterberg, Andreas; Kiening, Karl (World neurosurgery, 2019)
Objective - To assess early complications, mortality rate, and cement leakage in elderly patients who had undergone navigation-based pedicle screw placement of the thoracic and lumbar spine. - Methods - Eighty-six patients older than 65 years of age who had received cement-augmented pedicle screws for various conditions were retrospectively included between May 2008 and December 2016. Complications, mortality, and cement leakage were determined. All patients had a radiograph as a control. In patients with cement leakage seen on radiographs, a computed tomography scan of the surgical area was also obtained. - Results - Average age was 73.4 years (range 65-86 years). A total of 319 vertebral bodies with 637 screws were inserted, of which 458 screws were cement-augmented; 348 (76%) of the augmented screws were placed in the lumbar spine and 110 (24%) in the thoracic spine. Cement leakage occurred in 55 of 86 patients, of whom 52 (60%) were asymptomatic. In all cases with cement leakage (asymptomatic or symptomatic), cement could be found in the perivertebral veins: in the inferior vena cava in 25%, in the epidural space in 7%, in the azygos vein in 5%, and in pulmonary arteries in 7%. - Conclusions - Our study confirms that the use of cement correlates with a high risk of cement leakage in elderly patients. Using computed tomography navigation for screw placement did not reduce the risk of venous cement leakage, but leakage into the epidural space or through a cortical defect seems to be low.
Gesehen am 06.12.2019